Heuristic Approach to Urban Sprawl Recognition Using RS & GIS Techniques - Al-Mahfadi, Abdulbasit; Maiyas, Mohamed Ahmed (University of Science and Technology, Sana'a, 2007)
Urban sprawl is due to population growth, rural urban migration, lack of economic sustainable growth and poor urban and regional plans strategies. This paper presents a heuristic approach to urban sprawl recognition using remote sensing and GIS techniques. It discusses the processing of RS and GIS data for Sana a City (the capital of Yemen Republic) 1988, 1994 and 1998 in urban pattern recognition. Spatial and temporal urban changes are discussed in the analytical process of the urban sprawl recognition. The heuristic modeling for the identification and prediction of urban sprawl scenarios in Sana a is also discussed.